The Influence of the Internet on Study Interests of High School Students in Timor Leste - Jose Feliciano Lim Belo Ximenes; Febri Liantoni; Cucuk Wawan Budiyanto (Journal of Informatics and Vocational Education, 2023)
Several schools in big cities in Timor-Leste already have computers connected to the Internet; these computers are used for school administration and the learning process to facilitate the process of communication and data exchange; each computer must be connected to a wired or wireless network. With a sufficient internet network, I hope students can increase their interest in learning. In this regard, this study aims to explain the positive and negative effects of the Internet on high school students' learning interest in Timor Leste. This research uses a quantitative method, which will be filled with numbers and statistics that will then be described descriptively. Based on the results of this study it is supported by data and analysis of significant conditions, which means that the Internet used is what is expected of the learning interests of high school students in Timor-Leste. Based on the SPSS version 25 data processing test on F count, the results were obtained so that the internet variable (X1) simultaneously had a simultaneous impact on learning interest (Y) for high school students in Timor-Leste with an F test score of 17.614 and a significant level of 0.000. And sourced from the test of the coefficient of determination that the Internet (X1) has on the learning interest of high school students in Timor-Leste. The summary model value of R2 is 0.317.